The Bleeding Vale - Syed, Basharat Ali (Rawalpindi, Pakistan M/S Atiq Publishing House, 1991)
On the atrocities of the Indian army in Jammu and Kashmir.
Include Colour illustration and Appendix
Keywords: Political atrocities -- India--Jammu and Kashmir -- Politics and government